2016
DOI: 10.1016/s0140-6736(16)30579-7
|View full text |Cite
|
Sign up to set email alerts
|

The global burden of viral hepatitis from 1990 to 2013: findings from the Global Burden of Disease Study 2013

Abstract: Summary Background With recent improvements in vaccines and treatments against viral hepatitis, an improved understanding of the burden of viral hepatitis is needed to inform global intervention strategies. We used data from the Global Burden of Disease (GBD) Study to estimate morbidity and mortality for acute viral hepatitis, and for cirrhosis and liver cancer caused by viral hepatitis, by age, sex, and country from 1990 to 2013. Methods We estimated mortality using natural history models for acute hepatit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
1,019
0
40

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 1,217 publications
(1,067 citation statements)
references
References 26 publications
8
1,019
0
40
Order By: Relevance
“…It has been estimated that this will lead to 19 million deaths between 2015 and 2030 (11.8 million due to HBV and 7.2 million due to HCV) around the world. 23 In the present study, 22 cases (11%) developed cirrhosis or hepatocellular cancer.…”
supporting
confidence: 47%
See 2 more Smart Citations
“…It has been estimated that this will lead to 19 million deaths between 2015 and 2030 (11.8 million due to HBV and 7.2 million due to HCV) around the world. 23 In the present study, 22 cases (11%) developed cirrhosis or hepatocellular cancer.…”
supporting
confidence: 47%
“…1 Between 1990 and 2013, the number of deaths worldwide due to viral hepatitis increased from 0.89 million to 1.45 million. 23 In the absence of treatment, 20-30% of hepatitis B virus (HBV) and HCV-infected individuals will develop hepatocellular carcinoma or cirrhosis. It has been estimated that this will lead to 19 million deaths between 2015 and 2030 (11.8 million due to HBV and 7.2 million due to HCV) around the world.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The burden of disease owing to viral hepatitis has worsened, from being the tenth, to the seventh leading cause of death, between 1990 and 2013 [1]. This transition may have occurred owing to inaccessibility and/or lack of knowledge of the availability of regular screening, effective vaccines, and treatments, particularly among high-risk groups [2].…”
Section: Introductionmentioning
confidence: 99%
“…However, viral hepatitis has perhaps not been given as much spotlight as a health priority as other major infectious diseases (such as HIV and tuberculosis), despite the high morbidity and mortality associated with the consequences of this chronic infection: progressive liver disease, including cirrhosis and liver cancer. 1 has confirmed that viral hepatitis is one of the leading causes of death and disability worldwide, with at least as many deaths attributed to this infectious disease as HIV, tuberculosis or malaria. In fact, viral hepatitis now ranks as the seventh leading cause of global mortality.…”
mentioning
confidence: 95%